The relationship of the postural variable during the mycational act with the appearance of urogynecological disorders: an integrative review (Research, Society and Development, 2022)
The objective was to analyze the attitude adopted by women during the voiding act in situations of poor hygiene in public toilets and the relationship of the postural variable with the appearance of urogynecological problems. The present study was an integrative review, carried out with a search in different databases (Online Medical Literature Analysis and Retrieval System Online (MEDLINE®), Latin American and Caribbean Literature in Health Sciences (LILACS), Database in Nursing (BDENF) and in the Physiotherapy Evidence Database (PEDro), with the use of Descriptors in Health Sciences (DeCS): urination, posture, women's health and symptom assessment. There was a total of 01 article in MEDLINE, 03 articles in LILACS, 01 article in BDENF and 03 articles in PEDro.It is pointed out that the behavior adopted by women during the voiding act in public toilets and the appearance of urogynecological disorders are interconnected and directly related to behavioral factors when using public restrooms and environmental factors, thus causing the appearance of lower urinary tract symptoms. The role of a multidisciplinary team is important, offering health promotion, prevention, recovery and rehabilitation. It is understood that, despite the important findings of this study that will support actions aimed at urogynecological disorders, there are some limitations, such as the scarcity of studies applied to the subject, which leads to the need to optimize academic and scientific production in the area.